Statistical Analysis of Shrinkage Levels of Human Brain Slices Preserved by Sheet Plastination Technique with Polyester Resin [Análisis Estadístico de Los Niveles de Retracción de Cortes de Cerebro Humano Conservados Mediante la Técnica de Plastinación de Cortes Con Resina Poliéster] - Alarcon-Alvarez, E (Universidad de la Frontera, 2020)
Plastination is currently the most important anatomical preservation technique due to the possibility of preserving bodies and organs for an indefinite period, in a dry and biosecure form, while preserving the morphological characteristics of the tissues. However, the shrinkage of the samples is also part of the plastination, perhaps becoming one of its few disadvantages. This paper presents the shrinkage caused by the classic technique of sheet plastination with polyester resin (Biodur® P40) in human brain slices, with the aim of statistically establishing the percentages of tissue shrinkage caused by this plastination protocol. © 2019, Universidad de la Frontera. All rights reserved.